Application of metagenomic next-generation sequencing (mNGS) in diagnosing pneumonia of adults - Zhiguang Liu; Chuang Sun; Xinru Xiao; Lianzheng Zhou; Yanhua Huang; Yujia Shi; Xiaowei Yin; Zhengdao Mao; Qian Zhang (Journal of Infection in Developing Countries)
Introduction: Accurate identification of pathogens that cause pulmonary infections is essential for effective treatment and hastening recovery in adults diagnosed with pneumonia. At present, despite metagenomic next-generation sequencing (mNGS) technology has been widely used in clinical practice for pathogen identification, the clinical significance and necessity of detecting pathogen in bronchoalveolar lavage fluid (BALF) for pneumonia-stricken adults remain ambiguous.